Exploration on Technical Measures for Compaction Construction of Highway Engineering Roadbed and Pavement - Zhang, Jinchun; Zhang, Dongshui (Journal of Theory and Practice of Management Science, 2024)
The compaction of roadbed and pavement in highway engineering is an important process in the entire pavement construction. Adequate compaction of the roadbed and pavement structural layer is an important condition to ensure the strength of the roadbed and pavement, which is related to the quality of the entire construction and the service life after it is put into operation. If the compaction construction quality does not meet the standards, it will not only affect the actual application and durability of the project, but also increase traffic risks in highway applications. Therefore, attention must be paid to the compaction quality of the roadbed and pavement during construction. To achieve this, construction enterprises and personnel should strive to improve compaction technology and management level based on the specific situation of the construction site and local natural and geological conditions, and use relevant technical measures in a targeted manner. Only in this way can the overall quality of highway engineering be ensured. Therefore, it is necessary to conduct relevant research on the technical measures for compaction construction of roadbed and pavement in highway engineering.